Marine biology - Reseck, John, 1935- (Reston, VA. : Reston Publishing Co., 1979)
A basic marine biology textbook, introducing marine environments and covering the general principles of the field, including taxonomy and ecology.
Includes index.
Bibliography: p. 241-244.
Keywords: Marine biology